FDI location choice of Chinese multinationals in East and Southeast Asia: traditional economic factors and institutional perspective - Kang, Y.; Jiang, Fuming (Pergamon, 2012)
This paper investigates the factors determining foreign direct investment (FDI) location choices ofChinese multinational firms. We developed a conceptual framework that synthesizes traditionaleconomic factors and institutional perspective. Then several hypotheses were developed in line with theframework and empirically tested using panel data of Chinese outward FDI to eight economies in Eastand Southeast Asia across a time period of thirteen years. Our findings suggest that institutional factorsdemonstrate a higher level of significance, complexity and diversity in determining FDI location choice incomparison with economic factors, while both types of factors influence the FDI location choice ofChinese multinational firms. We also found that the FDI location choices of Chinese firms have a dynamic nature, as statistical evidence indicates a heterogeneous response of Chinese FDI towards different economic groups and during different time periods.